Internationalization of Higher Education in India: Benefits and Challenges (International Journal of Food and Nutritional Sciences, 2022)
Education paves way for success in one’s life. Designing such model of education to suit the modern society is a challenge. Indian system of education in the past has proved and developed moral and ethical skill set for the survival and success of human. For a nation to develop, Higher education is the backbone. For a developed country, Health, GDP, and education are the core parameters, for a developing nation like India we need to achieve them. Hence, this paper is an attempt to see India as a Vishwa guru in education. Bringing back old glory of India remembering Takshashila, Nalanda, Vikramshila, etc., where, Europeans, Chinese used to come and study in India. In this direction, Internationalization of Higher education in India, brings foreign direct investment in education, foreign eco-system into our country. However, there could be some hick-ups matching up the gaps between our educational eco-system and foreign education eco-system, and taking this as a challenge to meet such gaps the policy makers need to lay a pass over in this direction. This will reduce the brain-drain and invite foreigners to establish institutes such a Universities, research institutes and bring their people to study in India. This research study elucidates the need of internationalization of education in the Indian scenario. This exploratory research study aims to bring out the need, benefits and challenges faced in the transformation and transition faced by India in creating and modernizing the educational need with global standards. The objective of this study brings out the various steps taken by India to achieve the global standards in higher learning. In this direction Indian Government drafted National Educational Policy 2020.